Japanese Buddhism in Germany - Brandt, Laura; Prohl, Inken (Journal of Religion in Japan, 2022)
The following article describes the perceptions and practices of Japanese Buddhism in Germany, focusing on Zen and its local converts. We will give a short overview of the early reception of Buddhism in Germany, which shaped the foundation of its further development there. The article will then examine the relationship between the German reception of Japanese Buddhism and National Socialism and introduce Eugen Herrigel, who wrote the bestseller Zen in der Kunst des Bogenschießens, which led to increased interest in Buddhist practices. We will trace how institutionalization manifested in the Buddhist landscape in Germany, utilizing Deshimaru Taisen as an example. We will then briefly discuss the influence of Japanese Buddhism on philosophy, psychology, and popular culture. The conclusion will draw attention to the lack of attention to specific themes in previous discussions on Japanese Buddhism, especially on women’s activities in the field.
Volume 11, issue 1 ist gleichzeitg Special issue: Japanese Buddhism in Europe, part 2
Keywords: Geschichte 1600-2022; Rezeption; Zen-Buddhismus; Buddhismus; Japan; Deutschland